Soil Compaction Induced by Different Tillage Systems and its Impact on Growth and Yield of Maize (Zea Mays L.): Soil Compaction Induced by Different Tillage Systems and its Impact on Growth and Yield of Maize (Zea Mays L.): A Review - Nassir, aqeelnasssir; Mishall , Abbas; mohammed , ahmad (University of Thi-Qar Journal of agricultural research, 2024)
Abstract: Maize (Zea Mays L.) cultivation faces challenges from mechanized tillage-induced compaction, impacting soil physical properties crucial for growth. This compaction, stemming from machinery-soil interactions during tillage, alters bulk density, root penetration resistance, and water infiltration rates. Tractive tires play a central role in this process. The chapter explores the intricate relationship, emphasizing its adverse effects on maize root development, nutrient availability, and overall grain yield. While studies report significant yield reductions under severe compaction, a universally agreed-upon critical level remains elusive, necessitating further research into dynamic soil factors influencing maize productivity. This insight informs strategies for optimizing cultivation practices amid mechanized tillage challenges. Soil compaction, a critical concern in maize cultivation, profoundly impacts plant growth. Mechanized tillage-induced compaction alters soil properties, affecting bulk density, root penetration, and water movement. Compacted soil restricts air and water availability, hindering root respiration and nutrient uptake. This multifaceted constraint leads to poor seed germination, reduced yields, and increased vulnerability to root diseases. Mitigation strategies include low tillage machine loads, precision agriculture, conservation tillage, bioturbation, and deep tillage. While some compaction may benefit water retention, excessive levels pose risks. A holistic approach involves soil assessments, controlled traffic farming, cover crops, mechanical aeration, optimized equipment design, and ongoing monitoring. Education and adaptive practices are crucial for sustainable soil compaction management.